ANALISIS UNSUR INTRINSIK DAN UNSUR EKSTRINSIK NOVEL “DIA ADALAH KAKAKKU” KARYA TERE LIYE - Yantidiana Danur; Ida Ayu Made Wedasuwari; I Komang Widana Putra (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2021)
This study aims to describe the intrinsic and extrinsic elements in the novel Dia Is Kakakku by Tere Liye. The method in this research uses qualitative analysis methods. Based on the data analysis, the intrinsic elements contained in Tere Liye's novel Dia Is My Kakakku are (1) the theme in Tere Liye's Dia Is My Kakakku novel tells the love of an older brother, (2) the main character in Tere Liye's Dia Is my Kakakku novel. namely Laisa, while the additional characters are Mamak, Dalimunte, Ikanuri, Wibisana, Yashinta, Wak Burhan, Cie Hui. (3) The setting is divided into two, namely the setting of the place covering the Lahambay Valley, Jungle Forest, Upper Village, Sub-District City, river, house, schools, airports, hospitals and the time setting in this story is at 19:30 local time. (4) language style, namely metamonia language style, (5)